Determining whether Public Communications Campaigns Based on the The Social Norms Approach are a Viable COVID-19 Prevention Strategy for College Campuses. Issue 11 (2nd November 2021) - Smith, Sandi W.; DeJong, WILLIAM; Turner, Monique M.; Park, Sunyoung; Jang, Youjin; Poole, Andrew; Martell, Dennis; Salerno, Jordyn
Abstract : The purpose of this study is to (a) outline the formative steps that universities can follow to determine if a media campaign based on the social norms approach (SNA) is a viable method for increasing COVID-19 prevention behaviors among their students, (b) present formative research data collected at a large public land-grant university in the U.S., and (c) as a test case, apply that data to assess the SNA's viability for promoting COVID-19 prevention behaviors among students at that institution. Over time, a series of fast-track surveys were conducted to determine the descriptive and injunctive norms for four COVID-19 prevention strategies: wearing a mask in public, physical distancing, limiting the size of indoor gatherings, and receiving or planning to get a vaccination. The results demonstrated that, at this particular university, an SNA-based public communications campaign would be a promising strategy for promoting these protective behaviors. First, a clear majority of the survey respondents reported engaging in the behaviors. Second, the respondents perceived the behaviors to be less common than was actually the case, with one exception: wearing a mask. In all four cases, they perceived the behaviors to be less approved of than what the surveys documented.